Critical thinking and its importance in the present days for social workers - Belchior-Rocha, H. (2022)
Critical thinking is multidimensional, it encompasses the intellectual (logic, rationality), psychological (self-awareness, empathy), sociological (in terms of socio-historical context), ethics (norms and moral evaluation) and philosophical (meaning of nature and the human being). As a competency, or set of competencies, critical thinking can be developed and assessed. In this sense, the exploratory study that we intend to present aims to contribute to the evaluation of the importance that students attribute to critical thinking, as well as to the evaluation of critical thinking as a competence in the present situation. Before the pandemic situation we conducted a study with a universe of the 1st year social work students recently graduated, whose training included the critical thinking curricular unit in their study plan, we used as a data collection technician, a questionnaire with likert scale to measure the students opinions. The results were very positive and students admit that it helped them to analyze information (the importance of details), to practice curiosity and skepticism (to ask questions and compare with other sources) and to question (particularly, their own beliefs), including problem solving or decision making. With this recent challenge, consequence of Covid-19, it was necessary to alter all the previous model and adjust it to the pandemic situation through distance learning. Due to the characteristics of this curricular unit, we understand that in addition to the contents and usual dynamic, it was important to support students in adapting to the new methods and use this situation in favor of the benefits of thinking critically. Being a new situation for all (teachers and students) systematic evaluations were made to perceive if the results of the changes introduced were promoting the desired effect. Subsequently, in a total of 6 classes, with about 35 students each, we selected a non-probabilistic sample of 2 students of each class and each student was asked to make a critical assessment of the impact of this curricular unit in their learning process. Among other results that we intend to present, the key was to achieve a balance between the need for security and the need to know other ways of doing or thinking and classifying the critical thinking skills acquired as potentialities to support the uncertainty of the moment. This is where critical reflection (especially involving others) can play a key role in building trust by analyzing strengths-based practice, but it also allows considering alternative options, points of view, increase their ability to assess and position themselves in different contexts and learn to be prepared for unexpected situations.